Synthesis, Characterization and Gas Sensing Properties of Graphene Oxide-Multiwalled Carbon Nanotube Composite. Issue 7 (July 2016) - Kavinkumar, T.; Manivannan, S.
Abstract : Graphene oxide (GO)-multiwalled carbon nanotube (MWCNT) composite was synthesized and characterized by X-ray diffraction, atomic force microscopy, scanning electron microscopy, micro Raman, Fourier transform infrared and ultraviolet-visible near infrared spectroscopy techniques. Spectral characteristics of cladding modified fiber optic gas sensors were studied for various concentrations of ammonia, ethanol and methanol at 27 °C. Thickness of the gas sensing layer was controlled by varying the concentration of composite in ethanol medium (0.5 and 1 mg/mL) for three times dipping process. The 0.5 mg/mL concentrated GO-MWCNT coated sensor showed 1.20, 1.40 and 1.15 times higher sensitivity than the GO coated sensor for ammonia, ethanol and methanol vapors, respectively. Furthermore, it exhibited 1.50, 1.80 and 1.80 times better sensitivity than 1 mg/mL concentrated GO-MWCNT coated sensor for ammonia, ethanol and methanol vapors, respectively. The presence of functional groups in GO increased the sensitivity. This is mainly attributed to the effective electron charge transfer between the composite materials and analytes.